Analisis pengaruh investasi dan kesempatan kerja terhadap produk domestik bruto Indonesia - Kosiah, Kosiah; Nurjanah, Rahma; Artis, Dearmi (e-Journal Perdagangan Industri dan Moneter, 2018)
The aims of this study are: (1) to determine the development of investment, employment opportunities, and Gross Domestic Product; and (2) to analyze the effect of investment and employment opportunities on Indonesia's Gross Domestic Product. The data used in this study are secondary data sourced from the Indonesian Central Bureau of Statistics (BPS) Office. The data analysis method used is multiple linear regression.Based on the results of the analysis, it is known that (1) investment in Indonesia during the analysis period increased by an average of 20.46%, Indonesian employment opportunities during the period 2000-2017 increased by 1.77%, and Indonesia's GDP during the period 2000-2017 the average increased by 5.30%; and (2) simultaneously the variables of investment and employment have a significant effect on Indonesia's GDP, and partially investment and employment also have a significant effect on Indonesia's GDP. Keywords : Investment, Job opportunities, GDP